Operational atmospheric and wave modelling in the California's coastline and offshore area with applications to wave energy monitoring and assessment. Issue 2 (3rd April 2017) - Galanis, George; Kafatos, Menas; Chu, Peter C.; Hatzopoulos, Nikolaos; Papageorgiou, Evgenia; Liakatas, Aristotelis
ABSTRACT: A new high-resolution operational atmospheric/wave forecasting system for the west coastline of the US, focusing especially to the California near and offshore area, is presented in this work. The new system is the result of the collaboration between two US and one European Universities. It consists of two state-of-the-art numerical prediction models (Regional Atmospheric Modeling System and WAve Model) supported by a new optimisation statistical module for the bias reduction and local adaptation of the results based on non-linear Kalman filtering and Bayesian statistics. The presented system has been evaluated against a wide number of National Data Buoy Center buoys records with very promising results. Moreover, applications to wave energy site assessment are presented revealing areas of the California coastline with increased power potential appropriate for wave power plants installation.